THE EFFECT OF GROUP INVESTIGATION TECHNIQUE FOR ENGLISH SPEAKING PRACTICE - Mandayu, Yohana Yosiphanungkas Bahari; Sudarsono, Sudarsono; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe how the Group Investigation technique affects the class dynamic learning of English Speaking practice and how the Group Investigation technique affects the students’ cooperative learning in English Speaking practice by Year-10 students of SMA Negeri 3 Pontianak in Academic Year 2013/2014. This study is a case study. The subject in this study is the students of class 10F which consist of 35 students. This research uses observation, interview, and documentation technique. Data is analyzed using a formula to find out the percentage of class dynamic learning. The result of analysis shows the percentage of class dynamic learning 77.97% with criteria good learning. This result indicates that group investigation technique affect the students’ English speaking practice which is shown from the students’ positive response on every aspect being observed during the learning process. The result of interview indicates that Group investigation makes students work cooperatively in group and they can build a new relationship with people who culture and tradition are different from them Key Words: Group Investigation, Speaking Skill, Cooperative Learning